2021
DOI: 10.3390/ijms22147554
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dendritic Cell in Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) is one of the most significant microvascular complications in diabetic patients. DN is the leading cause of end-stage renal disease, accounting for approximately 50% of incident cases. The current treatment options, such as optimal control of hyperglycemia and elevated blood pressure, are insufficient to prevent its progression. DN has been considered as a nonimmune, metabolic, or hemodynamic glomerular disease initiated by hyperglycemia. However, recent studies suggest that DN is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Mast cells could promote renal fibrosis and inflammation, and thus implicated in the pathogenesis of DN ( 54 , 55 ). A recent study reported that DC plays an important role in the pathogenesis of DN ( 56 ). Therefore, we speculated the C1 subgroup is more likely to develop advanced DN than the C2 subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells could promote renal fibrosis and inflammation, and thus implicated in the pathogenesis of DN ( 54 , 55 ). A recent study reported that DC plays an important role in the pathogenesis of DN ( 56 ). Therefore, we speculated the C1 subgroup is more likely to develop advanced DN than the C2 subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…However, all DC subgroups do not cause the same pattern of pathological damage to the kidney, varying according to the type and stage of disease development and the activation of different subgroups of DCs. Transplantation of MSCs (mesenchymal stromal cells) into rats with diabetic nephropathy significantly reduced the levels of CD103+CDC1s, while decreasing the expression of inflammatory factors TNF-alpha and MCP-1, which in turn attenuated renal injury through the inactivation of CD8+ T cells 3 . Kidney-infiltrating CD4+ T cells can stimulate macrophages by producing cytokines such as TNF-alpha.…”
Section: Discussionmentioning
confidence: 99%
“…Glomerular damage is one of the main pathological features of DN. There is considerable evidence that inflammatory responses and infiltrating immune cells play an important role in the pathogenesis of diabetic nephropathy and disease progression through the immune system 3 . In addition, the range of responses generated by inflammation plays a key role in the development and progression of diabetic nephropathy and the modulation of inflammation and associated immune activity is emerging as a therapeutic strategy 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…T2DM is a serious public health issue with significantly increasing rates across the world. 24 As one of the most significant microvascular complications in diabetic patients, DN is considered a metabolic and hemodynamic glomerular disease initiated by hyperglycemia, 25 and the overproduction of various inflammatory factors is involved in the pathogenesis of DN. 26 The current understanding of diabetes-driven vascular complications as well as therapeutic interventions has arisen from studying disease pathogenesis in animal models.…”
Section: Discussionmentioning
confidence: 99%